2005
DOI: 10.1111/j.1365-313x.2005.02420.x
|View full text |Cite
|
Sign up to set email alerts
|

Cold‐inducible zinc finger‐containing glycine‐rich RNA‐binding protein contributes to the enhancement of freezing tolerance in Arabidopsis thaliana

Abstract: SummaryGlycine-rich RNA-binding proteins (GR-RBPs) have been implicated to play roles in post-transcriptional regulation of gene expression in plants under various stress conditions, but the functional roles of GR-RBPs under stress conditions remain to be verified. Here, we examine the biological roles of a GR-RBP, designated atRZ-1a, in Arabidopsis thaliana under stress conditions. atRZ-1a was expressed ubiquitously in various Arabidopsis organs including stems, roots, leaves, flowers, and siliques. The trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
147
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(152 citation statements)
references
References 40 publications
4
147
1
Order By: Relevance
“…2) (23). GR-RBPs have been shown to be involved in the plant's response to environmental stresses, particularly cold (45,46). However, little is known about the molecular function of either GR-RBPs or mRBPs.…”
Section: Discussionmentioning
confidence: 99%
“…2) (23). GR-RBPs have been shown to be involved in the plant's response to environmental stresses, particularly cold (45,46). However, little is known about the molecular function of either GR-RBPs or mRBPs.…”
Section: Discussionmentioning
confidence: 99%
“…atRZ1 mutants are more sensitive to low and freezing temperatures, whereas overexpressing plants are more tolerant to these stresses (Kim et al, 2005). On the basis of these results, Kim et al (2005) concluded that atRZ1 might have an RNA chaperone activity leading to the destabilization of the over-stabilized secondary structures and, thereby, to facilitate an efficient translation at low temperature. Another Arabidopsis protein involved in pre-mRNA processing and cold signaling is STA1.…”
Section: Post-transcriptional Regulation Of Cold Acclimation Responsementioning
confidence: 93%
“…Functional characterization of one Arabidopsis GR-RBP, the atRZ1, provided interesting data about the role of these proteins in cold acclimation (Kim et al, 2005). atRZ1 mutants are more sensitive to low and freezing temperatures, whereas overexpressing plants are more tolerant to these stresses (Kim et al, 2005). On the basis of these results, Kim et al (2005) concluded that atRZ1 might have an RNA chaperone activity leading to the destabilization of the over-stabilized secondary structures and, thereby, to facilitate an efficient translation at low temperature.…”
Section: Post-transcriptional Regulation Of Cold Acclimation Responsementioning
confidence: 97%
See 1 more Smart Citation
“…The amount of zinc finger protein in cells appears to be small under favorable conditions; however, transcription is increased and this protein is among the STREs when unfavorable conditions are encountered. Therefore, STRE-dependent transcriptional induction normally occurs rapidly (Kim et al 2005, Jang et al 2007). In the present study, expression of the gene coding for the zinc finger protein increased 2-fold after heat stress and this increase, together with the enhancement of some regulated factors, strengthened the defense of the organism and reduced the damage to cell function.…”
Section: Genes Related To Immunitymentioning
confidence: 99%